Caculus Differentiation Use the rules of differentiation to find the derivative of the function. f(x)=2x^3-4x^2+3x    

Expert Answers
sciencesolve eNotes educator| Certified Educator

You need to differentiate the given function with respect to x, such that:

`f'(x) = (2x^3 - 4x^2 + 3x)' `

`f'(x) = (2x^3)' - (4x^2)' + (3x)'`

`f'(x) = 2*3*x^(3-1) - 4*2*x^(2 - 1) + 3*1`

`f'(x) = 6x^2 - 8x + 3`

Hence, evaluating the derivative of the given function, yields `f'(x) = 6x^2 - 8x + 3.`

oldnick | Student

`d/dx( 2x^3-4x^2+3x)=6x^2-8x+3`